Mental health and quality of life in patients with premenstrual exacerbation: a cross-sectional study in Japan - Mariko Ogawa; Yukiko Iioka; Kiyoshi Takamatsu (Journal of Obstetrics and Gynaecology)
Background In the classification of premenstrual disorders (PMDs), premenstrual exacerbation (PME) is listed as one of the variants of PMDs, along with core PMD. However, the incidence of PME and its impact on mental health and quality of life have not been investigated. Therefore, we investigated the proportion of PME among women seeking treatment for premenstrual symptoms in Japan and compared the levels of anxiety, depression and quality of life between women with PME and those with core PMD.Methods Women who presented to the Department of Obstetrics and Gynaecology of a single institute for treatment of premenstrual symptoms and were diagnosed with PMDs using patient diaries were included in the study. Based on the diagnosis, patients were divided into two groups (core PMD and PME) and their responses to a questionnaire on mental health and quality of life at the first visit were analysed.Results A total of 32 women were diagnosed with PMDs (22 with core PMD and 10 with PME). All underlying medical conditions in women with PME were psychiatric disorders. There were no significant differences in various factors between the two groups. In terms of mental health, the PME group had higher levels of anxiety and depression than the core PMD group. Regarding quality of life, the PME group had lower scores than the core PMD group in all domains except physical and social functioning.Conclusions Patients seeking treatment for premenstrual symptoms included many PME. Women with PME were more anxious and depressed than those with core PMD, and their quality of life was low in both physical and psychological domains. Patients with PME should be diagnosed and treated more appropriately.